Konsep Ruang Sakral dan Profan Pasar Gawok - Iskandar, Dedi; Sardjono, Agung Budi; ., Wijayanti (Universitas muhammadiyah palembang, 2019)
The purpose of this study examines the concept of the sacred space and profane of Gawok market Sukoharjo which was formed and grew because of the beliefs held between the Gawok community and the previous King Kasunanan. From this belief, traditions and cultures are created, such as the determination of the Pon market day, the Angon Putu Tradition, the Sesajen Jum’at Ritual, the Kulo Nuwun Ritual, the Nyuwun Pitedah Ritual, and the Ngubur Blanjan Ritual. Qualitative research methods are used to explore and observe research objects in depth and then describe the state of cultural traditions such as places, social behavior, activities, market activities that are not yet known specifically for analysis of the influence of the concept of sacred and profane spaces that form a market tradition. The result of this concept is to create a local cultural identity and character of local wisdom and the noble norms of the Gawok market to make the market survive and exist until now amidst current penetration and modernization.